RESTAURATIVE JUSTICE: SOUTHERN EPISTEMIC EMERGENCIES TO COMBAT DOMESTIC VIOLENCE AGAINST BLACK WOMEN IN BRAZIL (Publicatio UEPG: Ciências Sociais Aplicadas, 2022)
This article investigates if the Restorative Justice is an appropriate justice paradigm to face domestic violence against black women in Brazil. The objective is to show that the vertical model of criminal justice perpetuates the colonial project of subordination and victimization of women, especially black women, throught the invisibilization of their narratives, that can be demonstrated through data shown throughout the text. The article seeks to evidence that is needed a justice paradigm that does not embrace the imposition of pain (penalty) as a response to the conflict, as well to evidence the potentiality and risks of applying Restorative Justice in cases involving domestic violence, especially against black women. Therefore, it is understood that if the restorative practice is not methodologically parameterized by the epistemologies of the south, it takes the risk of satisfying uniquely the elite. Therefore, the epistemologies of brazilian black feminism are claimed. The research is qualitative and inductive, through the analysis of data made available by government agencies. Futhermore, this article concludes that black feminism aggregates the necessary epistemological contribution so that the restorative practices meet the needs of black women, victims of domestic violence in Brazil.